PHASE TRANSITION OF ZIRCON AT HIGH P-T CONDITIONS - Ono S.; Funakoshi K.; Nakajima Y.; Tange Y.; Katsura T. (My University, 2004)
In situ observations of the zircon-reidite transition in ZrSiO4 were carried out using a multianvil high-pressure apparatus and synchrotron radiation. The phase boundary between zircon and reidite was determined to be P (GPa) = 8.5+0.0017×(T-1200) (K) for temperatures between 1100–1900 K. When subducted slabs, including igneous rocks and sediments, descend into the upper mantle, the zircon in the subducted slab transforms into reidite at pressures of about 9 GPa, corresponding to a depth of 270 km. Reidite found in an upper Eocene impact ejecta layer in marine sediments is thought to have been transformed from zircon by a shock event. The peak pressure generated by the shock event in this occurrence is estimated to be higher than 8 GPa.
Keywords: zircon; reidite